Growth of aligned ZnO nanowires via modified atmospheric pressure chemical vapor deposition - Zhao, Yuping; Li, Chengchen; Chen, Mingming; Yu, Xiao; Chang, Yunwei; Chen, Anqi; Zhu, Hai; Tang, Zikang (Physics letters. A, 2016)
In this work, we report the growth of high-quality aligned ZnO nanowires via a facile atmospheric pressure chemical vapor deposition (CVD) method. The CVD reactor chamber used was more complicated than a conventional one due to the quartz boats loaded with sources (ZnO/C) and substrates being inserted into a semi-open quartz tube, and then placed inside the CVD reactor. The semi-open quartz tube played a very important role in growing the ZnO nanowires, and demonstrated that the transportation properties of Zn and O vapor differ from those in the conventional CVD reactor chamber. Aligned ZnO nanowires were successfully obtained, though they were only found at substrates located upstream. The very high crystalline quality of the obtained ZnO nanowires was demonstrated by high-resolution transmission electron microscopy and room temperature photoluminescence investigations. Such ZnO nanowires with high crystalline quality may provide opportunities for the fabrication of ZnO-based nano-devices in future. •High-quality aligned ZnO nanowires were obtained via modified chemical vapor deposition under atmospheric pressure.•The semi-open quartz tube plays very important roles in growing ZnO nanowires.•The transportation properties of Zn and O vapor differ from those in the conventional CVD reactor chamber.